Monetary Policy Effect on Lending Behaviour of Nepalese Commercial Banks - Pangeni, Sudip; Subedi, Kapil Deb (BIC Journal of Management, 2025)
This study explores how monetary policy influences lending behavior among commercial banks in Nepal, with particular attention to three primary tools: the cash reserve ratio, open market operations, and the bank rate. This research applies a quantitative design, drawing on panel data from eight commercial banks over a ten-year span (2014/15 to 2023/24). To assess the relationship between monetary policy instruments and bank lending behavior measured through the Credit-to- Deposit Ratio (CDR) Pearson correlation and multiple regression analysis were conducted using SPSS. The findings show that open market operations contribute positively to the Credit-to-Deposit Ratio, suggesting a supportive effect on lending activity. In contrast, a higher cash reserve ratio appears to constrain lending. These findings emphasize the role of liquidity-based instruments in directing how monetary policy is implemented and how effectively it supports financial stability in Nepal. The bank rate appears to have a rather muted and unpredictable influence, indicating that relying on interest rate adjustments may not be particularly effective for policy in this local setting. Bank size has a moderate influence on lending patterns, though the age of the bank doesn't have any major effect in this regard. These findings suggest the need to recalibrate monetary tools in favor of liquidity management over conventional interest rate adjustments. The findings indicate that targeted support for smaller banks, along with improvements in financial infrastructure particularly through the wider use of digital banking may help ensure that policy measures reach intended groups more effectively. These efforts could ease access to credit for individuals and businesses that often face financial barriers. Future research could explore how lending practices affect different areas of the economy and examine the role that new financial technologies are beginning to play in shaping Nepal’s banking environment.